THE EFFECT OF AUDIOVISUAL EDUCATION ON INTEREST IN THE UTILIZATION OF DENTAL HEALTH SERVICES DURING THE COVID 19 PANDEMIC - Hafidzani Hafez Widawati; Quroti A’yun; Hari Wibowo (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Interest in dental check-ups at dental health care facilities during the pandemic has decreased based on data from the Sukamara Regional General Hospital the number of visits from 572 patients in 2019 after the pandemic to 337 in 2020 and 198 patients from January–July 2021. Education audiovisual to increase interest in dental check-ups in dental health care facilities during the covid 19 pandemic. Objective: determine the effect of audiovisual education on interest in dental health check. s Method: Types This research is a quasi-experimental design with a non-equivalent control group. The study was carried out in March-April 2022. Sampling using purposive sampling technique with a sample of 80 people. Data analysis using Wilcoxon test. How to collect data with a questionnaire and the type of data taken is primary data. Results: Characteristics of 41 male respondents and 39 female respondents. The Wilcoxon test showed a p of 0.00 (p<0.005) and Mann Whitney testSig value = 0.015 (Sig <0.05) which is significant. Conclusion: There is an effect of audiovisual education on interest in dental health checks in dental services for respondents during the Covid 19 pandemic.